Effectiveness of Maitland Mobilization versus Pain release phenomena for pain, range of motion and disability in early knee osteoarthritis - Saeeda Taj, Kinza Anwar, Hafsah Arshad, Maria Khalid, Mohammad Qasim Ali, Ejaz Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the effectiveness of Maitland mobilization and pain release phenomena for Pain, Range of motion disability in early knee osteoarthritis. Methodology: Randomized control trail was conducted at Department of Physical Therapy, Railway General Hospital, Rawalpindi, Pakistan within a duration of 6 months. Participants aged between 35-60 years including both genders, diagnosed with stage 1 and 2 knee osteoarthritis were included. Range of motion (ROM) was assessed by Goniometer, Numeric pain rating scale(NPRS) used for pain and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores used for knee disability. IBM SPSS 24 was used for statistical analysis. Non-parametric tests were used for NPRS while parametric test were used for knee ROM and knee disability . Results: Total 47 participants, were analyzed in which mean age in Experimental Maitland mobilization group A was 45.3±6.06 while mean age in experimental pain release phenomena group B was 45.4±4.59. Between-group analysis for NPRS was significantly improved at post intervention having p value (0.03). Between group comparison of knee ROM and WOMAC also showed significant p value. (p value=<0.05). Conclusion: It is concluded that both techniques are equally effective in decreasing pain, improving knee ROMs and functional mobility in early knee osteoarthritis. Keywords: Knee Osteoarthritis; Early Mobilization ; Knee Joint Pain; Knee Joint Range Of Motion; Knee Disability.